Prescribing-Assessment Tools for Long-Term Care Pharmacy Practice: Reaching Consensus through a Modified RAND/UCLA Appropriateness Method - Gonçalves, João R. (2021)
Supplementary Materials - The following are available online at https://www.mdpi.com/article/10.3390/pharmacy9040194/s1, Table S1: Summary of the identified Prescribing-Assessment Tools.